URGENSI BAHASA ARAB DALAM TINJAUAN ILMU TANZILIYAH - Hakim, Luqman; Manzilah, Farah Diana; Kholil, Ahmad (Dar el-Ilmi : Jurnal Studi Keagamaan, Pendidikan dan Humaniora, 2023)
Arabic is the language of communication for Muslims. Arabic is the language of the Qur'an which has many features. Therefore, to understand the contents of the Qur'an, humans need to master Arabic well. In the Qur'an it has been explained about Islamic scientific orientation including tanziliyah science. To understand the knowledge contained in the Qur'an, Arabic appears as a tool and means for humans to understand it. The purpose of this study is to find out how the urgency of Arabic is in Islamic scientific orientation in terms of the tanziliyah aspect. This study uses a qualitative approach with descriptive analysis method. This study uses two data sources. That includes primary and secondary data. The analysis technique and also data collection in this study is to use a documentation study. The results of this study indicate that Arabic has a very important urgency in reviewing the tanziliyah aspect. Mastery of Arabic in the orientation of tanziliyah knowledge is very important in the implementation of worship to Allah SWT.